An improvement of surfactin production by B. subtilis BBG131 using design of experiments in microbioreactors and continuous process in bubbleless membrane bioreactor. (October 2016) - Motta Dos Santos, Luiz Fernando; Coutte, François; Ravallec, Rozenn; Dhulster, Pascal; Tournier-Couturier, Lucie; Jacques, Philippe
Highlights: Highthroughput approach and DoE to optimize surfactin production by B. subtilis. Highlight the medium limiting element impacting surfactin specific production. Investigate optimized media for continuous production of surfactin in BMBR. Abstract: Culture medium elements were analysed by a screening DoE to identify their influence in surfactin specific production by a surfactin constitutive overproducing Bacillus subtilis strain. Statistics pointed the major enhancement caused by high glutamic acid concentrations, as well as a minor positive influence of tryptophan and glucose. Successively, a central composite design was performed in microplate bioreactors using a BioLector®, in which variations of these impressive parameters, glucose, glutamic acid and tryptophan concentrations were selected for optimization of product-biomass yield (YP/X ). Results were exploited in combination with a RSM. In absolute terms, experiments attained an YP/X 3.28-fold higher than those obtained in Landy medium, a usual culture medium used for lipopeptide production by B. subtilis . Therefore, two medium compositions for enhancing biomass and surfactin specific production were proposed and tested in continuous regime in a bubbleless membrane bioreactor. An YP/X increase of 2.26-fold was observed in bioreactor scale.